Eliptične funkcije - Jenko, Izak (Matrika, 2022)
This paper discusses the basic theory of elliptic functions, which are doubly periodic meromorphic functions on the complex plane. A few examples of elliptic functions are constructed and afterwards focus shifts to the Weierstrass elliptic function ?$\wp$?. Laurent expansion of ?$\wp$? around the origin is derived, where Eisenstein series are also introduced. Lastly it is shown, that ?$\wp$? along with its derivative parametrizes a certain elliptic curve over the field of complex numbers.
Keywords: complex numbers; eliptične funkcije; elliptic functions; kompleksna števila; lastnosti; properties; Weierstrass elliptic function; Weierstrassova funkcija